SYNTHESIS OF IMINODIACETIC ACID IN A CASCADE REACTOR (Hungarian Journal of Industry and Chemistry, 2001)
The present paper deals with the modernization of the manufacturing of iminodiacetic acid, enhancing the conversion and the reactor-intensity, as well as with the elaboration of a procedure permitting continuous production. During the investigation of the industrial synthesis of iminodiacetic acid our important recognition is that glycine, produced together with the desired iminodiacetic acid, can be converted with monochloroacetic acid to iminodiacetic acid after removal of the excess of ammonia from the reaction mixture. For utilization of glycine, an industrial procedure has been elaborated. According to this, production of iminodiacetic acid is carried out in a quadrate cascade reactor, so that the reaction mixture leaving the second reactor element is freed from ammonia, concentrated, and then reacted with an equivalent of monochloroacetic acid calculated on the basis of the glycine-content. In this way, iminodiacetic acid is obtained in the laboratory-scale experimental reactor with a 91% yield, based on monochloroacetic acid. Calculations for the optimization of the reactor-cascade are also presented. These clearly prove that the required new investment is reimbursed upon manufacturing on an industrial scale.
Keywords: iminodiacetic acid; reactor-cascade; optimization